Relevansi Keteladanan Tenaga Pendidik dalam Tradisi Pendidikan Islam Perspektif Ulama Tafsir - Muthiah, Annisa; Mujahada, Kharis Syuhud (Kuttab: Jurnal Ilmu Pendidikan Islam, 2025)
This study examines the concept of exemplary educators in Surah Al-Ahzab verse 21 through the interpretations of At-Thobari, Fakhrur Rozi, and Ibn ‘Ashur, focusing on the relevance of the Prophet Muhammad’s model (uswah hasanah) to modern education. Using a library research method and content analysis, the study finds that the three tafsir works offer complementary insights: At-Thobari stresses noble character and professional development, Fakhrur Rozi highlights justice and empathy, and Ibn ‘Ashur emphasizes leadership and moral formation. These findings affirm the Prophet’s example as a practical and holistic guide for value-based Islamic education, both theoretically and in practice.